Increasing Burden of Nursing Care on the Treatment of COVID-19 Patients in the Aging Society: Analyses During the First to the Third Wave of Pandemic in Kyoto City, Japan - Fujita, Kohei; Kashihara, Eriko; Kanai, Osamu; Hata, Hiroaki; Yasoda, Akihiro; Odagaki, Takao; Mio, Tadashi (Frontiers in Medicine, 2021)
Background: COVID-19 pandemic is associated with a heavy burden on patients’ mental and physical health, regional healthcare resources, and global economic activity. An ageing society such as Japan has many retirement homes and long-term stay hospitals for the elderly and their inhabitants. During the COVID-19 pandemic, disease clusters are often identified in retirement homes and long-term stay hospitals. Although we hypothesize that additional burdens of nursing care for elderly patients will reinforce the anxiety and exhaustion of medical staff and healthcare resources in the ageing society, the actual situation is not well understood. In this study, we aimed to evaluate the current situation and countermeasures of the COVID-19 pandemic in the ageing society. Methods: We reviewed COVID-19 patients who required hospitalization between 1 April 2020 and 31 March 2021. We assessed the characteristics of the COVID-19 patients, disease severity, duration of hospitalization, outcome at discharge, degree of activities of daily living (ADLs), and complications unique to elderly patients. Results: We enrolled 118 patients who required hospitalization during the study period. Approximately 40% of the patients were aged ≥ 80 years. Dementia (27.1%) was the most prevalent underlying disease, followed by diabetes mellitus (23.7%) and chronic kidney disease (23.7%). Approximately 60% of hospitalized COVID-19 patients had impaired ADL at admission. The COVID-19 patients aged 80 years or older required significantly more longer-term hospitalization than the COVID-19 patients aged under 80 years (15.5±8.2 vs. 13.1±7.7, P=0.032). In elderly patients aged 80 years or older, approximately 50% of patients had geriatric mental disorders, and approximately 70% had bedridden status and feeding difficulty. Poor ADL at admission was significantly associated with COVID-19 mortality (Odds ratio, 5.6; 95% confidence interval, 1.04-45.2; p value = 0.044). Conclusions: The proportion of elderly patients aged 80 years or older was relatively high during the hospitalization for COVID-19. Poor ADL at admission in these elderly patients was significantly associated with poor prognosis of COVID-19. We should keep in mind that healthcare workers are forced to have an additional burden of nursing care in the ageing society during the COVID-19 pandemic. Therefore, interventions to reduce the burden are urgently required.